Signs of Conflict: A Peircean Semiotic Study of Ja’far in Qalbu al-Lail - R. Zamzami Aulia; Rohanda Rohanda; Wildan Taufiq (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
This study aims to describe the portrayal of Ja 'far's internal conflict in Naguib Mahfouz's novel Qalbu Al-Lail through a semiotic analysis guided by Charles Sanders Pierce's framework and supplemented by Sigmund Freud's psychoanalytic theory. Ja' far's conflict is manifested through dialogue, actions, and symbols that reflect his struggle between personal desires, moral values, personal convictions, and familial expectations during the process of identity formation. The research employs a qualitative descriptive methodology; data sources include the novel Qalbu Al-Lail, with specific materials comprising dialogue excerpts, character behaviors, narrative elements, and symbols related to Ja' far's inner conflicts. Data were collected via literature review, reading analysis, and note-taking techniques. Analysis was conducted using Charles Sanders Pierce's semiotic model—including representation, object, and interpreter—and further enriched by Sigmund Freud's concepts of the id, ego, and superego. The research findings indicate that Ja 'far's inner conflict is portrayed as a tension between his desires, moral principles, and the realities of life, which gives rise to a crisis of identity. This study is expected to enrich the study of Arabic literature, particularly by integrating Pierce's semiotics with Freudian psychoanalytic theory to elucidate the meaning of the character's conflicts.